Integrasi Edukasi Lingkungan dan Praktik Biokonversi Limbah Organik melalui Budidaya Cacing Merah di Kelompok Wanita Tani - Syahidah, Tazkiyatul; Triwahyuningsih, Nike (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Organic waste from households and livestock remains a significant environmental challenge in rural areas. If not properly managed, such waste has the potential to cause environmental pollution; however, it also offers opportunities to be converted into value-added and economically beneficial products. This community service activity aimed to enhance community knowledge and skills in organic waste management through the production of livestock manure compost and the cultivation of red worms (Lumbricus rubellus). The implementation methods included educational outreach, demonstrations, and hands-on practices conducted with the Guyub Rukun Women Farmer Group (Kelompok Wanita Tani/KWT) in Selogedong Hamlet, Argodadi Village, Sedayu District, Bantul Regency. The results indicated an improvement in participants’ understanding of organic waste bioconversion concepts, practical skills in compost production and red worm cultivation, as well as increased interest in developing these activities into environmentally based productive enterprises. This activity contributes to supporting sustainable organic waste management while simultaneously creating opportunities for community economic improvement.